Radiological Assessment of Renal Length in Children - Widhodho T. Karyomanggolo (Indonesian Pediatric Society, 1990)
Assessment of kidney length to other easily available parameters such as L1-L3 length and age in the evaluation and care of growing children with kidney disease is a prerequisite. Eighty nine IVP photos were selected from children with urinary tract infection. Radiological examinations were done after the absence of clinical and laboratory abnormalities. Nine or 10.1% IVP photos had radiological abnormalities so they were excluded from this study. There was no difference in kidney length between boys and girls. There was a difference in length between the right and the left kidney. Strong correlation was found between kidney length and L1-L31ength, age, body he1ght and body weight. Tables are presented for charting data on kidney length and will be of use by pediatricians, radiologists and urologists in the care of growing children with kidney ailments.